1992
DOI: 10.1007/bf00602363
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid response to exercise as measured by serum and salivary cortisol

Abstract: Serum and salivary cortisol concentrations were studied in 78 elite athletes engaged in different sports, by subjecting them to high-intensity laboratory exercise. The mean difference in the pre-exercise cortisol concentrations in the seven groups studied were more marked in serum (from 311 to 768 nmol.l-1) than in saliva (from 17.9 to 22.7 nmol.l-1, only one group reaching 40 nmol.l-1). Judging from the correlation coefficients based on total variances, the post-/pre-exercise differences in cortisol concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 9 publications
3
27
0
Order By: Relevance
“…The collection procedure is easy, non-invasive, stress free, and it can be applied under a variety of field settings. Salivary levels accurately reflect the unbound, biologically active, hormonal fraction in the general circulation (Riad-Fahmy et al 1987;Vining et al 1983); pertinently, an excellent correlation was found between serum and salivary levels of cortisol as a response to an acute bout of maximal exercise (O'Connor and Corrigan 1987;Port 1991;Stupnicki and Obminski 1992;Thuma et al 1995).…”
Section: Introductionmentioning
confidence: 93%
“…The collection procedure is easy, non-invasive, stress free, and it can be applied under a variety of field settings. Salivary levels accurately reflect the unbound, biologically active, hormonal fraction in the general circulation (Riad-Fahmy et al 1987;Vining et al 1983); pertinently, an excellent correlation was found between serum and salivary levels of cortisol as a response to an acute bout of maximal exercise (O'Connor and Corrigan 1987;Port 1991;Stupnicki and Obminski 1992;Thuma et al 1995).…”
Section: Introductionmentioning
confidence: 93%
“…Despite these associations, we are aware of few investigations directly comparing plasma and salivary IL-6 concentrations (Minetto et al 2005;Minetto et al 2007). If salivary IL-6 concentrations provide a valid representation of plasma IL-6, in the same way that salivary cortisol is accepted as reXecting free (unbound) plasma cortisol concentrations (Stupnicki and Obminski 1992), then this would oVer an alternative to the invasive collection procedures currently required for monitoring IL-6 responses to exercise. Minetto et al (2005) examined plasma and salivary IL-6 concentrations in a small sample (n = 7) of athletes from varying sports.…”
Section: Introductionmentioning
confidence: 99%
“…While this seems a robust finding in individuals with established CFS, without prospective studies of individuals at high risk of developing CFS it is difficult to tell whether such changes play a causal role, or are a result of downstream factors such as sleep, deconditioning or circadian rhythm disruption (Spath Schwalde et al 1992;Stupnicki & Obminski, 1992 ;Leese et al 1996).…”
Section: Introductionmentioning
confidence: 99%